2018
DOI: 10.1175/jas-d-17-0213.1
|View full text |Cite
|
Sign up to set email alerts
|

Ultraclean Layers and Optically Thin Clouds in the Stratocumulus-to-Cumulus Transition. Part I: Observations

Abstract: A common feature of the stratocumulus-to-cumulus transition (SCT) is the presence of layers in which the concentration of particles larger than 0.1 μm is below 10 cm−3. These ultraclean layers (UCLs) are explored using aircraft observations from 14 flights of the NSF–NCAR Gulfstream V (G-V) aircraft between California and Hawaii. UCLs are commonly located in the upper part of decoupled boundary layers, with coverage increasing from less than 5% within 500 km of the California coast to ~30%–60% west of 130°W. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 64 publications
17
88
0
Order By: Relevance
“…Figure 3 shows the climatology of the fraction of low clouds that are optically thin veil clouds f thin,veil from CALIOP (i.e., cloud conditional fraction). One possible explanation for such equatorward decrease in f thin,veil is that since Wood et al (2018) andO et al (2018) suggested that the detrainment mechanism from deep Cu underneath the trade inversion is the key process for the formation of optical thin veil clouds, the boundary layer over the tropics may be unfavorable for the formation of optical thin veil clouds because the inversion becomes weaker and may not preferentially concentrate the location in the vertical of detrainment levels (see Figure 2). Over the northeast pacific (NEP), f thin,veil increases westward from below 0.1 east of 135 ∘ to ∼0.3 over the SCT region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3 shows the climatology of the fraction of low clouds that are optically thin veil clouds f thin,veil from CALIOP (i.e., cloud conditional fraction). One possible explanation for such equatorward decrease in f thin,veil is that since Wood et al (2018) andO et al (2018) suggested that the detrainment mechanism from deep Cu underneath the trade inversion is the key process for the formation of optical thin veil clouds, the boundary layer over the tropics may be unfavorable for the formation of optical thin veil clouds because the inversion becomes weaker and may not preferentially concentrate the location in the vertical of detrainment levels (see Figure 2). Over the northeast pacific (NEP), f thin,veil increases westward from below 0.1 east of 135 ∘ to ∼0.3 over the SCT region.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above formula and the mean LWP of thin veil clouds estimated based on aircraft in situ measurements (≈25 g m −2 ), Wood et al (2018) showed that for a threshold optical depth of 3 below which the lidar can penetrate, droplet concentration must be below approximately 20 cm −3 , indicating that low optical thickness of veil clouds is strongly contingent on their low droplet concentrations. Based on the above formula and the mean LWP of thin veil clouds estimated based on aircraft in situ measurements (≈25 g m −2 ), Wood et al (2018) showed that for a threshold optical depth of 3 below which the lidar can penetrate, droplet concentration must be below approximately 20 cm −3 , indicating that low optical thickness of veil clouds is strongly contingent on their low droplet concentrations.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In previous versions, the minimum CDNC (CDNCmin) was set to 40 cm −3 . The justification for this choice was twofold: first, while observations of clouds with a lower CDNC exist (e.g, Terai et al, 2014;Wood et al, 2018), these smaller concentrations normally occur in clouds or pockets in clouds that are much smaller than our grid boxes. Second, so far we do not account for nitrate aerosols and our treatment of secondary organic aerosols is rather simplistic and likely underestimates the organic aerosol concentration (Zhang et al, 2012).…”
Section: Aerosol and Cloud Microphysics Schemementioning
confidence: 99%